Crucial role of pre-treatment in plastic photoreforming for precision upcycling - Xiandi Zhang; Wenhan Zu; Lawrence Yoon Suk Lee (npj Materials Sustainability)
Abstract The accumulation of non-degradable plastics poses a significant environmental challenge. Photoreforming presents a promising solution through plastic upcycling. This review explores the mechanisms of photoreforming that determine product selectivity, emphasizing the role of polymer molecular structure and pre-treatment techniques. By identifying key factors affecting reaction dynamics, we aim to establish optimized frameworks for plastic photoreforming and enhance sustainable waste management, highlighting opportunities for improvement and innovation.